2016
DOI: 10.1073/pnas.1524360113
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a lay theory before college narrows achievement gaps at scale

Abstract: Previous experiments have shown that college students benefit when they understand that challenges in the transition to college are common and improvable and, thus, that early struggles need not portend a permanent lack of belonging or potential. Could such an approach-called a lay theory intervention-be effective before college matriculation? Could this strategy reduce a portion of racial, ethnic, and socioeconomic achievement gaps for entire institutions? Three double-blind experiments tested this possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
384
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 383 publications
(431 citation statements)
references
References 32 publications
16
384
0
3
Order By: Relevance
“…Andersen and Nielsen (2016) find similar results on test scores of an intervention targeting parents of primary school children in Denmark. In contrast to these positive results, one of the implementations studied in Yeager et al (2016b) found no effect on college enrolment of a growth-mindset intervention targeted at secondary school students. The lack of effects is possibly due to their target population consisting of high school students at high performing schools who have already been admitted to college.…”
Section: Growth Mindset Feedbackmentioning
confidence: 78%
See 2 more Smart Citations
“…Andersen and Nielsen (2016) find similar results on test scores of an intervention targeting parents of primary school children in Denmark. In contrast to these positive results, one of the implementations studied in Yeager et al (2016b) found no effect on college enrolment of a growth-mindset intervention targeted at secondary school students. The lack of effects is possibly due to their target population consisting of high school students at high performing schools who have already been admitted to college.…”
Section: Growth Mindset Feedbackmentioning
confidence: 78%
“…We note that the study by Paunesku et al (2015) potentially suffers from selection bias because as little as 3% of the students in participating schools are part of the study. However, other studies using online growth-mindset interventions have had almost complete coverage at participating schools and found similar results on grades, continued college enrolment or academic performance some time later (Yeager et al, 2016a;Yeager et al, 2016b;Bettinger, Ludvigsen, Rege, & Scolli, 2018). Bettinger et al (2018) showed that positive effects mainly arose for students who originally had a fixed mindset i.e.…”
Section: Growth Mindset Feedbackmentioning
confidence: 82%
See 1 more Smart Citation
“…Third, research suggests that psychological processes have an important role in how people respond to adversity. A sense of optimism, purpose, and belonging can improve long-term educational and health outcomes even among the economically disadvantaged (8)(9)(10)(11)(12). The importance of psychological processes in no way lessens the imperative to reduce poverty, discrimination, and other structural disadvantages.…”
mentioning
confidence: 99%
“…Randomized experiments conducted during transitions to middle school (13)(14)(15), high school, and college (11,12,16,17) have shown that brief interventions that support adaptive psychological processes improve grades and school retention. They do so by encouraging students to reflect on core values (13)(14)(15), by assuring them of their belonging in school (11,12), by highlighting the personal relevance of academic coursework (16), or by cultivating the belief that intelligence is malleable rather than fixed (11,17). No study, however, has shown that a psychological process altered at one transition has persistent and direct causal effects on outcomes at later transitions and in new institutions years later, and, if this does occur, how.…”
mentioning
confidence: 99%